Invasive species and irrigated agriculture in the western U.S. Issue 2 (24th May 2016) - DiVittorio, Joseph
Abstract : Agriculture in western U.S. States is highly dependent on irrigation, and the greatest volume of this water is supplied by surface sources that are vulnerable to infestation by aquatic invasive species. This article briefly discusses several familiar aquatic invasive species and then will proceed in greater detail to discuss more recently introduced species. Earn 1.5 CEUs in Integrated Pest Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/766 .